Failure analysis of 3D woven spacer sandwich composites with woven cross-links and face sheet thickening under compressive and flexural loading. (October 2021) - Neje, Ghanshyam; Behera, Bijoya Kumar
The effect of face sheet thickening on the mechanical properties of sandwich structures reinforced with 3 D woven spacer fabrics having woven cross-links has been presented in this work. Spacer fabrics forming cells of rectangular (RECT), trapezoidal (TPZ) and triangular (TR) shapes were used as reinforcement of sandwich structures with non-thickened face sheets. While for thickened face sheet structures, additional layers of 2 D fabric were integrally woven with the top and bottom face sheets of spacer fabrics, having almost similar cell geometrical parameters as that of the former structures, in a single step of weaving. Composites manufactured from these structures were characterized for their out-of-plane compressive and flexural properties. The specific compressive load was observed to be lower for thickened face sheet structures. The flexural load was higher for thickened face sheet structures; but the specific bending load decreased for the same. Flexural stress was also found to decrease with thickening of the face sheets. The results obtained could be helpful in designing sandwich composites connected woven fabric cross-links with enhanced mechanical properties.